Effect of Impact and Fruit Harvesting Indexes on the Quality of Mangosteen Fruit - I.B.P Gunadnya; I.M. Supartha Utama; M. Sudiana Mahendra (PERTETA, 2001)
Mangosteen fruit is one of tropical exotic fruits that has potency as exported commodity but its potency is limited by its poor quality. Both the fruit shell and its aril are very susceptible to any improver handling during and after harvesting andsince then its quality decreases rapidly. Experiments were set up to study the effect of impact, by dropping the fruit from certain heights, and fruit harvesting indexes on its quality. Visual observations showed that dropping the fruit from 0.5 m above the floor was sufficient to damage fruit shell and aril. The inner surface of fruit shell that subjected to the impact became brown and the aril became translucent and tasteless. Quantitatively, fruit shell became hard after two-day- storage and the dropping of the fruit and fruit harvesting indexes significantly affected total soluble solid of the aril. The fruit with harvesting index 5 significantly contained the less total soluble solid when it was dropped from the height of 1 m and stored for 6 days.